ANALISIS IMPLEMENTASI DIPLOMASI INDONESIA - MYANMAR DALAM KONFLIK ROHINGYA (TINJAUAN PERSPEKTIF FEMINISME) - Cecilia Henny, - (2018)
This study discusses about analysis of the implementation of Indonesian diplomacy with Myanmar related to the Rohingya conflict. The diplomation of Indonesia and Myanmar to be interesting when both actors from each country are a women with positions that are influential in the making of a policy and the policies formulated by these two woman actors result in a positive resolution without having to using hard power diplomacy. Researcher used three theories that are related to each other that is constructivism, feminism and diplomacy. Methods using qualitative methods that emphasize descriptively, exploratory and analysing extracting information and data about implementation of Indonesia- Myanmar diplomacy related to Rohingya conflict. The results showed that the diplomacy that played by women not always will lead to failure but it can provide a cooperative policy